2019
DOI: 10.1038/s41598-019-52464-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Pulsed Electric Fields for the preparation of Spanish dry-cured sausages

Abstract: The aim of this investigation was to lay the groundwork of the potential application of Pulsed Electric Fields (PEF) technology for accelerating the drying process of meat and meat products, and specifically in this work of Spanish dry-cured sausages “longaniza”. PEF treatments were applied to pork loin samples, and the influence of different PEF parameters on the process were evaluated. An optimal PEF treatment of 1 kV/cm, 200 μs of pulse width and 28 kJ/kg was determined as the most suitable to electroporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Although PEF processing has been used as a pretreatment in the dried food industry for diverse vegetables ( 20 , 32 35 ). Nevertheless, there are few previous works on the effect of PEF as a pretreatment for the drying process in matrices of animal origin; however, an investigation carried out by Astráin-Redín et al ( 20 ) reported a reduction in the curing time of Spanish sausage between 19 and 33% when applying PEF as a pretreatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PEF processing has been used as a pretreatment in the dried food industry for diverse vegetables ( 20 , 32 35 ). Nevertheless, there are few previous works on the effect of PEF as a pretreatment for the drying process in matrices of animal origin; however, an investigation carried out by Astráin-Redín et al ( 20 ) reported a reduction in the curing time of Spanish sausage between 19 and 33% when applying PEF as a pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…The thermophysical properties so far published have served to increase the database as well as to allow and test the mathematical models that depend on the composition, temperature, pressure, orientation of the fiber, etc. ( 20 ). As for the food microstructure, its evaluation depends on the processing method, the operating variables, and the microstructure of the food produced during the process ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…As already known, in pulsed electric field technology, high-intensity electric fields (> 0.1 kV/cm) are applied to the meat between two electrodes for a very short time (in the range of milliseconds to microseconds) [49]. The most important phenomenon associated with PEF is the occurrence of electroporation, which increases the juiciness of the meat [50].…”
Section: Production and Processingmentioning
confidence: 99%
“…The most important phenomenon associated with PEF is the occurrence of electroporation, which increases the juiciness of the meat [50]. Another advantage is the minimal effect on the microstructure of the meat [50], while shortcomings include the strong dependence on intrinsic factors of the treated food/meat which may reduce its effectiveness [49].…”
Section: Production and Processingmentioning
confidence: 99%
“…These reports found that when an electric field is applied on cells, the thermal fluctuation introduced hydrophobic pores that can evolve into larger hydrophilic pores on the cell membrane by rearranging polar molecules in the phospholipid bilayer to minimize free energy. These electroporated pores allow the ions and molecules to be transported into or out of the cells, enabling medical applications such as DNA electrotransfer [20], electrochemotherapy [21], drug delivery [22], therapeutic healing [1,14,[17][18][19], DNA vaccination [23,24], sampling target cells for monitoring [25][26][27], industrial applications in food processing [28,29], and cell inactivation [30]. Moreover, electroporation method exhibits a simple and efficient way compared with other membrane-disruption based methods such as mechanical methods by physically puncturing [31] or deformation in microfluidic channel [32], and thermal heating by laser [33] as well as nanocarrier-based delivery through biological endocytosis and fusion [34,35].…”
Section: Introductionmentioning
confidence: 99%